Learning Obstacles dalam Pembelajaran Aritmetika Sosial pada Siswa Sekolah Menengah Pertama - Sumiaty, Encum; Anugerah, Marvel Hegi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to find out what Learning Obstacles are experienced by junior high school students in learning social arithmetic. The method used in this research is qualitative method. Participants consisted of seven research subjects from various state and private schools in Bandung City. Data was collected through offline tests and interviews. The results of this research show that there are at least two types of learning obstacles experienced by students, namely ontogenic obstacles and epistemological obstacles which can be seen from the students' inability to translate questions and the students' inability to master the prerequisite material. Conclusion: From the research that has been conducted, there are learning obstacles for junior high school students in social arithmetic material. The identified learning obstacles are ontogenic obstacles and epistemological obstacles. Therefore, it is very important to analyze what learning obstacles are experienced by students so that solutions can be found to reduce these learning obstacles. In terms of students, they also need to improve their mathematical literacy to be able to overcome the learning obstacles experienced by students. Keywords : Learning Obstacles, Social Arithmetic, Study Of Mathematic